2020
DOI: 10.1007/s10120-019-01036-5
|View full text |Cite
|
Sign up to set email alerts
|

Utility of continuous glucose monitoring following gastrectomy

Abstract: Background Glucose fluctuation after gastrectomy represented by dumping syndrome is a well-known post-gastrectomy syndrome that negatively impacts patient quality of life. However, the current methods of post-gastrectomy glucose monitoring do not comprehensively capture the postoperative blood glucose fluctuations that characterize this. Methods We used a continuous glucose monitoring (CGM) system to document the glycemic profiles of patients undergoing gastrectomy and compared these between patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…To our knowledge, this is the first exploratory study of real-time changes in glucose profiles when a dumping symptom actually occurs after gastrectomy using CGM and daily recording of diet and symptoms. Although a few studies have demonstrated continuous glucose profiles using CGM after GC surgery, with most simply measuring the glucose fluctuations, the occurrence of dumping symptoms over time has not previously been examined[ 22 - 24 ]. Results of the present study indicated glucose fluctuations to be involved in the onset of late dumping as well as early dumping symptoms after standard gastrectomy for GC.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first exploratory study of real-time changes in glucose profiles when a dumping symptom actually occurs after gastrectomy using CGM and daily recording of diet and symptoms. Although a few studies have demonstrated continuous glucose profiles using CGM after GC surgery, with most simply measuring the glucose fluctuations, the occurrence of dumping symptoms over time has not previously been examined[ 22 - 24 ]. Results of the present study indicated glucose fluctuations to be involved in the onset of late dumping as well as early dumping symptoms after standard gastrectomy for GC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TG-RY showed lower postprandial glycemic levels following glucose spikes, and the hypoglycemic period with glucose <70 mg/dL during CGM measurement was longer in the TG-RY group than in the other three procedure groups. Using CGM, Kubota et al demonstrated nocturnal hypoglycemia after TG-RY in gastric cancer [ 28 ]. In addition, several hypoglycemic episodes after RY gastric bypass in obese patients have been reported to be asymptomatic [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, among the clinical patient factors, distal gastrectomy was an independent factor associated with “non-dumper” (dumping score of 4 or below) and the degrees of postprandial increases in blood glucose, GLP-1, and GLP-2 levels and heart rate were significantly more prominent in patients with total gastrectomy than those in patients with distal gastrectomy. Previous studies reported higher incidences of early dumping syndrome in patients who underwent total gastrectomy than those in patients who underwent distal gastrectomy due to more accelerated nutrient delivery into the small intestine [ 1 29 ]. To our knowledge, this is the first study to identify a significant difference in the degree of postprandial changes in GI hormones and hemodynamics between patients who underwent distal or total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%